anonymous
  • anonymous
Solve for s. -2s – 19 = 6s + 13
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
@MollyNicole2015
anonymous
  • anonymous
\[-2s-6s=13+19\]\[-8s=32\]
MollyNicole2015
  • MollyNicole2015
Simplifying -2s + -19 = 6s + 13 Reorder the terms: -19 + -2s = 6s + 13 Reorder the terms: -19 + -2s = 13 + 6s Solving -19 + -2s = 13 + 6s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-6s' to each side of the equation. -19 + -2s + -6s = 13 + 6s + -6s Combine like terms: -2s + -6s = -8s -19 + -8s = 13 + 6s + -6s Combine like terms: 6s + -6s = 0 -19 + -8s = 13 + 0 -19 + -8s = 13 Add '19' to each side of the equation. -19 + 19 + -8s = 13 + 19 Combine like terms: -19 + 19 = 0 0 + -8s = 13 + 19 -8s = 13 + 19 Combine like terms: 13 + 19 = 32 -8s = 32 Divide each side by '-8'. s = -4 Simplifying s = -4

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

MollyNicole2015
  • MollyNicole2015
Now what do you do to verify it's right?
anonymous
  • anonymous
Put the answer back into the equation.
confxsedaf
  • confxsedaf
@MollyNicole2015 is correct :)
MollyNicole2015
  • MollyNicole2015
Right! Do it.
MollyNicole2015
  • MollyNicole2015
:) Thanks
anonymous
  • anonymous
-2 x -4 – 19 = 6 x -4 + 13 -2 x -4 - 19 = -11 6 x -4 + 13 = -11 -11 = -11
MollyNicole2015
  • MollyNicole2015
Good! So that means what?
anonymous
  • anonymous
Our equation is correct.
MollyNicole2015
  • MollyNicole2015
Very good!
anonymous
  • anonymous
I'm going to medal you because you're so good at helping. :)
MollyNicole2015
  • MollyNicole2015
Thank you. <3 And you deserve a medal for your hard work!

Looking for something else?

Not the answer you are looking for? Search for more explanations.